2020
DOI: 10.4081/ija.2020.1648
|View full text |Cite
|
Sign up to set email alerts
|

Grain yield and associated physiological traits of rapeseed (<em>Brassica napus L.</em>) cultivars under different planting dates and drought stress at the flowering stage

Abstract: The adverse effects of abiotic stresses have always restricted oilseed crop production, particularly in arid and semi-arid regions. On the other side, global climate change has led us to adapt planting dates and select tolerant cultivars to encounter the new climatic conditions. To evaluate the effect of late-season drought stress under different planting dates on rapeseed cultivars, an experiment was conducted as a factorial split-plot based on randomized complete block design in Karaj region- Iran, during 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Furthermore, the late sowing of winter rapeseed reduced the rapeseed yield, and early flowering was also significantly affected by CS. Moreover, intracellular ice crystals are formed due to CS, distorting the sensitive plant organs (Lardon and Triboi-Blondel, 1995;Raza, 2020a;Shafighi et al, 2020). New seedlings, flowering, and seed formation are also mainly affected by CS (Lardon and Triboi-Blondel, 1995;Shafighi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the late sowing of winter rapeseed reduced the rapeseed yield, and early flowering was also significantly affected by CS. Moreover, intracellular ice crystals are formed due to CS, distorting the sensitive plant organs (Lardon and Triboi-Blondel, 1995;Raza, 2020a;Shafighi et al, 2020). New seedlings, flowering, and seed formation are also mainly affected by CS (Lardon and Triboi-Blondel, 1995;Shafighi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, intracellular ice crystals are formed due to CS, distorting the sensitive plant organs (Lardon and Triboi-Blondel, 1995;Raza, 2020a;Shafighi et al, 2020). New seedlings, flowering, and seed formation are also mainly affected by CS (Lardon and Triboi-Blondel, 1995;Shafighi et al, 2020). In recent studies, it was found that CS significantly reduced survival rate by impairing different physiobiochemical (reduced antioxidant enzyme activities, osmolyte content, and phytohormone levels) and molecular (reduced transcript levels of CS-responsive marker and antioxidant genes) mechanisms (Yan et al, 2019;He et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Canola plants at low densities produced more floral branches and were less efficient in producing seeds per unit of invested pod wall (non-seed reproductive biomass) compared with plants at relatively high densities (Figure 1d). Biomass allocation to seed and pod wall was higher in the main floral raceme than in floral branches (Shafighi et al, 2021;Wang et al, 2021).…”
Section: Yield In Response To Increasing Population Densitymentioning
confidence: 88%
“…Canola growth and biomass yield were sensitive to plant population density and environmental conditions (Behrens and Diepenbrock, 2006;Li et al, 2018). Although more resources were used by each canola plant under low plant densities, such resources would be applied to luxury vegetative growth at an individual level without increasing above-ground dry matter and hence seed yield per unit area (Shafighi et al, 2021;Zhang et al, 2020). Therefore, a reasonable increase in plant density can curtail such luxurious vegetative growth of individuals (Rathke et al, 2006;Ren et al, 2017).…”
Section: Yield In Response To Increasing Population Densitymentioning
confidence: 99%
See 1 more Smart Citation